Incidence of thrombosis and hemorrhage in hospitalized cancer patients with COVID‐19. (23rd August 2020) - Patell, Rushad; Bogue, Thomas; Bindal, Poorva; Koshy, Anita; Merrill, Mwanasha; Aird, William C.; Bauer, Kenneth A.; Zwicker, Jeffrey I.
Abstract: Background: Coronavirus disease‐2019 (COVID‐19) is a recognized prothrombotic state. Patients hospitalized with active cancer are predisposed to thrombosis but whether active cancer further amplifies thrombotic risk with COVID‐19 is not known. Objectives: To evaluate cumulative incidences of thrombotic and hemorrhagic events in hospitalized COVID‐19 patients with and without active cancer at 28 days. Methods: A retrospective cohort analysis of consecutive adults hospitalized with COVID‐19 was performed. Active cancer required cancer‐directed therapy within previous 6 months. The cumulative incidences of thrombosis or hemorrhage were estimated considering death as a competing risk. Results: Patients without cancer (n = 353) and active cancer (n = 45) were comparable in terms of age, sex, antibiotics administered, length of hospitalization, and critical care. The most common malignancies were lymphoid (17.8%), gastrointestinal (15.6%), lung (13.3%), and genitourinary (13.3%). At day 28, the cumulative incidence of thrombotic events was 18.2% (95% confidence interval [CI], 10.2%‐27.9%) in the non‐cancer cohort and 14.2% (95% CI, 4.7%‐28.7%) in the cancer cohort. The cumulative incidence of major and fatal bleeding at day 28 was 20.8% (95% CI, 12.1%‐31.0%) in the non‐cancer group and 19.5% (95% CI, 5.5%‐39.8%) in the cancer cohort. Three patients experienced fatal bleeds, all of whom were in the non‐cancer cohort. Survival was significantly shorter in the group with active cancer ( P  = .038). Conclusions: We observed a similarly high incidence of thrombosis and bleeding among patients admitted with COVID‐19 with or without active cancer.